2015
DOI: 10.3329/bjp.v10i1.21068
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid regulates Wnt/β-catenin signaling pathway and CDK8 in HCT 116 and HT 29 colon cancer cells

Abstract: Research ArticleEllagic acid regulates Wnt/ Ellagic acid regulates Wnt/ Ellagic acid regulates Wnt/β β β---catenin catenin catenin signaling pathway and CDK8 in HCT signaling pathway and CDK8 in HCT signaling pathway and CDK8 in HCT 116 and HT 29 colon cancer cells 116 and HT 29 colon cancer cells 116 and HT 29 colon cancer cells BJP IntroductionColorectal cancer is the second most frequent malignancy and the second leading cause of death due to cancer globally (Walker et al., 2014). Colon cancer carcinogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…In the present study, we decided to determine the mRNA expression of Wnt target genes, such as anti-apoptotic survivin (BIRC5), cell-cycle regulators, namely cyclin D1 and c-myc. A number of earlier studies indicate that higher expression of these genes occurs in various cancers, including colorectal cancer [44,45]. In the present study we showed that the inhibition of growth and migration in Caco-2 cultures treated with SPF may be associated with downregulation of pro-survival genes.…”
Section: Discussionsupporting
confidence: 70%
“…In the present study, we decided to determine the mRNA expression of Wnt target genes, such as anti-apoptotic survivin (BIRC5), cell-cycle regulators, namely cyclin D1 and c-myc. A number of earlier studies indicate that higher expression of these genes occurs in various cancers, including colorectal cancer [44,45]. In the present study we showed that the inhibition of growth and migration in Caco-2 cultures treated with SPF may be associated with downregulation of pro-survival genes.…”
Section: Discussionsupporting
confidence: 70%
“…The induction of apoptosis was accompanied PI3K/Akt pathway. Along with production of ROS and release of cytochrome c. Recent studies showed that ellagic acid modulates Wnt/b-catenin pathway and CDK8 activity in colon cancer cells (HT 29 and HCT 116) (Fang et al 2005). Ellagic acid caused significant decrease in viability of cancer cells and markedly down-regulated the expression of CDK 8, b-catenin, survivin, c-Myc and cyclin D1.…”
Section: Ellagic Acid and Colon Cancermentioning
confidence: 99%
“…Anitha and others found that EA treatment suppressed the Wnt/β-catenin pathway in an animal model of oral oncogenesis (Anitha et al, 2013). In another in vitro study, EA inhibited the Wnt/β-catenin pathway in colon cancer cells (Fang et al, 2015). Similar to these two studies, our work showed the inhibitory effect of EA on the Wnt/β-catenin pathway, and further demonstrated that this pathway was involved in EA-induced suppression of the pathological phenotypes of ATC cells (Fig.…”
Section: Discussionmentioning
confidence: 94%